Exploration of the production of three Thiodiketopiperazines by an endophytic fungal strain of Cophinforma mamane - Pacheco-Tapia, Romina (2023)
Endophytic fungi possess a versatile metabolism which is related to their ability to live in diverse ecological niches. While culturing under laboratory conditions, their metabolism is mainly influenced by the culture media, time of incubation and other physicochemical factors. In this study, we focused on the production of 3 thiodiketopiperazines (TDKPs) botryosulfuranols A−C produced by an endophytic strain of Cophinforma mamane isolated from the leaves of Bixa orellana L collected in the Peruvian Amazon. We studied the time-course production of botryosulfuranols A−C during 28 days and evaluated the variations in the production of secondary metabolites, including the TDKPs, produced by C. mamane in response to different culture media, light versus dark conditions and different incubation times. We observed a short time-frame production of botryosulfuranol C while its production was significantly affected by the light conditions and nutrients of the culture media. Botryosulfuranols A and B showed a similar production pattern and a similar response to culturing conditions. Molecular networking allowed us to detect three compounds related to TDKPs that will be the focus of future experiments.